Morpho-physiological and Production Responses of Peanut (Arachis hypogaea L.) to Biostimulant Protein Hydrolysate Under Drought Stress - Mufida, Zida Ilmi; Setiawati, Tri Candra; Siswoyo, Tri Agus (European Journal of Applied Sciences, 2025)
Abiotic stress has been demonstrated to exert a deleterious effect on plant growth and development, culminating in diminished crop yields. This phenomenon has also been observed in peanuts. Among the various types of abiotic stress, drought is considered the most critical, as limited water availability has a negative impact on plant growth and development, especially in arid and semi-arid regions. This study aims to assess the impact of applying a protein hydrolysate biostimulant on the morphological, physiological, and production responses of groundnuts (Arachis hypogaea L.) variety ’Takar-2’ under drought conditions. The observed parameters included plant height, root length, number of nodules, percentage of active nodules, chlorophyll a, b, total chlorophyll content, relative water content, and number of pods. The findings indicated that the application of protein hydrolysate led to substantial enhancements in the morphological adaptation of the plants, as evidenced by an increase in plant height, root length, and nodule number. Additionally, the application improved physiological parameters, including chlorophyll a and b, total chlorophyll, and relative water content. Furthermore, utilizing biostimulants positively affected the number of pods under drought conditions. Consequently, protein hydrolysate has the potential to function as a biostimulant, thereby enhancing the resilience and yield of groundnuts in environments with limited water availability.